A method for activating the surface of a non-conductive substrate or a carbon fiber-containing substrate for metallization.

JP2026530355APending Publication Date: 2026-09-08ATOTECH DEUT GMBH & CO KG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2026508782
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-07
Filing Date
2024-09-03
Publication Date
2026-09-08

AI Technical Summary

Benefits of technology

【0035】 加えて、信頼性を著しく向上させつつ、堆積された金属層の被覆状態及び接着性も維持する又は向上させることができた。このことは、製造プロセスにおける品質の問題を回避するものである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026530355000001
    Figure 2026530355000001
  • Figure 2026530355000002
    Figure 2026530355000002
  • Figure 2026530355000003
    Figure 2026530355000003
Patent Text Reader

Abstract

The present invention relates to a method for treating the surface of a non-conductive substrate or a carbon fiber-containing substrate, comprising: (I) a step of conditioning the surface of the non-conductive substrate or the carbon fiber-containing substrate, the conditioning method comprising: (a) a step of preparing the substrate; (b) a step of preparing a conditioning composition containing a nitrogen-containing compound; and (c) a step of contacting the substrate with the conditioning composition to obtain a conditioned surface; (Ia) a step of rinsing the surface of the non-conductive substrate or the carbon fiber-containing substrate, the rinsing method comprising: (a) a step of preparing the substrate treated according to step (I); (b) a step of preparing an aqueous acidic rinsing composition; and (c) a step of contacting the substrate with the aqueous acidic rinsing composition to obtain a rinsed surface; and (II) a selective agent for the surface of the non-conductive substrate or the carbon fiber-containing substrate. The processing steps include a method for selective agent processing, comprising: (a) a step of preparing the substrate processed according to step (I); (b) a step of preparing a selective agent composition comprising (i) a nitrogen-containing compound and (ii) having a pH of 9 to 14; and (c) a step of contacting the substrate with the selective agent composition; and (III) a step of activating the surface of a non-conductive substrate or a carbon fiber-containing substrate, wherein the activation method includes: (a) a step of preparing the substrate processed according to step (II); (b) a step of preparing a palladium-free aqueous activating composition comprising (i) a first type of dissolved transition metal ion and additionally its metal particles; (ii) one or more types of complexing agents; and (iii) one or more types of reducing agents permanently or temporarily; and (iv) optionally, one or more second types of dissolved metal ions different from the first type. At least one type of dissolved transition metal ion and its metal particles exist in a reversible equilibrium state, wherein - the metal particles are formed from the dissolved transition metal ion by continuous or semi-continuous reduction with one or more reducing agents, - the dissolved transition metal ion is formed from the metal particles by continuous or semi-continuous oxidation of the particles, and -The present invention relates to a step in which dissolved transition metal ions and their metal particles repeatedly participate in the reduction and oxidation, respectively, so as not to form aggregates on which the metal particles precipitate, and a method comprising (c) contacting the substrate with the activating composition so that a transition metal or transition metal alloy is deposited on the surface of the substrate and an activated surface for metallization is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

[[Technical Field]]

[0001] The present invention generally relates to activating the surface of a non-conductive substrate or a carbon fiber-containing substrate for subsequent metallization.

[0002] In particular, the present invention relates to a method for activating the surface of a non-conductive substrate or a carbon fiber-containing substrate for metallization, and a method for metallizing the activated surface of a non-conductive substrate or a carbon fiber-containing substrate. [[Background Art]]

[0003] Metallization of such substrates is of high commercial interest. In many aspects of daily life, such substrates are coated with metallic structures or layers for either decorative or functional applications. For example, non-conductive plastic substrates are typically used in the manufacture of sanitary articles provided with a glossy chromium layer. Furthermore, the automotive industry also uses a very large number of plastic substrates coated with chromium.

[0004] In addition to such decorative articles, functional metallization is indispensable, for example, in the manufacture of printed circuit boards. For such boards, a non-conductive resin-containing laminate is typically used as the base material, which usually contains copper wire circuits.

[0005] Carbon fiber-containing substrates are increasingly gaining potential as catalytically active surfaces, for example, in power-to-gas, power-to-fuel, and power-to-chemical applications, as well as in batteries.

[0006] All these applications require that non-conductive substrates or carbon fiber-containing substrates are usually subjected to multi-step preparation to make them receptive to subsequent metallization.

[0007] In the first step, the surface of the non-conductive substrate or the carbon fiber-containing substrate is usually cleaned, for example, to remove grease or impurities.

[0008] In the second step, the surface is typically conditioned (also called pre-treatment) to make it receptive to subsequent activation.

[0009] In the third step, a crucial activation takes place. In such activation, a very thin seed layer or activation layer is typically deposited / fixed onto the surface of a non-conductive substrate or carbon fiber-containing substrate, which acts as a starting point for the subsequent first metallization layer. The result is an activated surface for metallization. The seed layer or activation layer typically acts as a mediator between the surface of the non-conductive substrate or carbon fiber-containing substrate and one or more subsequent metallization layers. Typically, the seed layer / activation layer is formed by depositing metal nanoparticles onto the surface, for example, from a colloidal activation composition.

[0010] In the fourth step, the first metallized layer is typically deposited on the seed / activation layer, most commonly by electroless plating. In some cases, this electroless plating involves immersion plating, i.e., the deposition of more noble metals on the seed / activation layer by exchange reaction in the absence of a reducing agent. In other cases, it involves the deposition of metal or metal alloy by autocatalytic deposition, which means that deposition is accelerated by a reducing agent.

[0011] In the fifth step, typically, a second metallized layer is deposited on the first metallized layer again by autocatalytic deposition or electrodeposition.

[0012] In principle, those skilled in the art are well familiar with such a series of processes. Typically, in common colloidal activating compositions, precious metal nanoparticles are used, very often as palladium nanoparticles. However, precious metals are generally expensive, and wastewater treatment for reusing residual precious metals is a major concern. Alternatively, less expensive metal ions are increasingly being used in each activating composition.

[0013] For example, Chinese Patent Application Publication No. 107460459 relates to a simple nanocopper activating solution using a stabilizer and a reducing agent to prevent aggregation and oxidation of nanoparticles, respectively.

[0014] U.S. Patent No. 4,278,712 discloses a method for activating a weakly active colloidal dispersion useful for preparing nonconductive materials before electroless plating. This method is based on the controlled oxidation of a colloid that is weakly active in its natural state, by treatment with appropriate gases and / or chemical agents that result in said controlled oxidation. However, the presence of at least one colloidal stabilizer is essential. In this method, reversible equilibrium is not maintained.

[0015] A common drawback is that such activated compositions spontaneously undergo a certain degree of degradation or decomposition. Typically, nanoparticles aggregate to form insoluble precipitated aggregates, rendering the composition largely unusable. Therefore, it is typically desirable to stabilize the nanoparticles after they have been formed by the reduction of each metal ion. For this purpose, stabilizer compounds are usually used to alter the charge distribution of the particles, limit their particle size, and / or prevent oxidation of the particles. Often, polymers and / or antioxidants and / or metal ions (such as tin ions) are used for these purposes.

[0016] Methods described in this technical field typically have the disadvantage of being prone to aggregation and precipitation sooner or later, primarily because the stabilizing compound does not adequately stabilize the particles over time. As a result, product life is highly dependent on the production date, delivery time, and the quality of stabilization.

[0017] Furthermore, such stabilizing compounds are thought to often reduce the ability of nanoparticles to effectively activate each surface. While the additives may, on the one hand, prevent aggregation to some extent, on the other hand, they appear to inhibit the rapid and strong adsorption of these particles onto the surface.

[0018] WO 2020 / 201387 discloses a method for activating the surface of a non-conductive substrate or a carbon fiber-containing substrate for metallization and respective activating compositions, and it is disclosed that the composition is simple and highly effective on one hand, and on the other hand, is particularly less prone to cause aggregation and precipitation, and a long shelf life is ensured.

[0019] WO 2022 / 043417 discloses a method of activating the surface of a non-conductive substrate or a carbon fiber-containing substrate for subsequent metallization, wherein a conditioning step is followed by a selecting agent treatment step, and then an activating step is performed. The selecting agent step improves the results of a solder shock test at 288°C.

[0020] It has been found that metallized substrates produced by such processes exhibit inferior performance or unstable performance in solder shock tests. Furthermore, performance problems when using prior art methods have been observed in applications with high thermal stress.

Prior Art Literature

Patent Literature

[0021]

Patent Document 1

Patent Document 2

Patent Document 3

Patent Document 4

Summary of the Invention

Problem to be Solved by the Invention

[0022] Therefore, it is an object of the present invention to provide an improved method for activating the surface of a non-conductive substrate or a carbon fiber-containing substrate for metallization, which method is on the one hand simple and highly effective, on the other hand is particularly less prone to agglomeration and precipitation, and ensures a long shelf life. Furthermore, such methods and respective compositions should be low-cost.

[0023] Another object of the present invention was to provide respective methods with reduced environmental impact, exemplified by involving less extensive wastewater treatment and a reduction in the effective concentration of chemical substances.

[0024] Another object of the present invention was to provide respective methods that exhibit good and stable performance in a standard solder shock test at 288°C.

[0025] Furthermore, another object of the present invention is to pass the solder shock test at 326°C with a lower defect rate, which is more frequently required by customers to ensure higher reliability of the formed interconnections even under high thermal stress conditions.

[0026] Still another object of the present invention was to provide improved electrical reliability of copper-copper (Cu-Cu) interconnections in printed circuit boards. Means for Solving the Problems

[0027] The aforementioned object is achieved by a method of treating the surface of a non-conductive substrate or a carbon fiber-containing substrate, wherein the method comprises: (I) a step of conditioning the surface of a non-conductive substrate or a carbon fiber-containing substrate, wherein the conditioning method comprises: (a) providing the substrate, (b) providing a conditioning composition comprising a nitrogen-containing compound, and (c) contacting the substrate with the conditioning composition to obtain a conditioned surface a step comprising (Ia) A step of rinsing the surface of a non-conductive substrate or a carbon fiber-containing substrate, wherein the rinsing method is (a) A step of preparing the substrate processed according to step (I), (b) A step of preparing an aqueous acidic rinse composition, and (c) A step of bringing the substrate into contact with the aqueous acidic rinsing composition to obtain a rinsed surface. Processes including (II) A step of selective agent treatment of the surface of a non-conductive substrate or a carbon fiber-containing substrate, wherein the selective agent treatment method is (a) A step of preparing the substrate processed according to step (Ia), (b) (i) Contains nitrogen-containing compounds, (ii) Having a pH of 9-14 The process of preparing a selective agent composition, and (c) A step of bringing the substrate (the substrate treated according to step (Ia)) into contact with the selective agent composition. Processes including, and (III) A step of activating the surface of a non-conductive substrate or a carbon fiber-containing substrate for metallization, wherein the method of activation is: (a) A step of preparing the substrate processed according to step (II), (b) (i) Dissolved transition metal ions of the first species and additionally their metal particles, (ii) One or more complexing agents, and (iii) one or more reducing agents, permanently or temporarily, and (iv) Optionally, one or more dissolved metal ions of a second species different from the first species. This is a step to prepare a palladium-free aqueous activated composition containing the following: - At least one species of dissolved transition metal ions and their metal particles exist in a reversible equilibrium state, provided that, - Metal particles are formed from dissolved transition metal ions by continuous or semi-continuous reduction with one or more reducing agents. - The dissolved transition metal ions are formed from metal particles by continuous or semi-continuous oxidation of the particles, and - The dissolved transition metal ions and their metal particles repeatedly participate in the reduction and oxidation processes, respectively, so that aggregates on which the metal particles precipitate do not form. Process, and (c) A step of bringing the substrate (the substrate treated according to step (II)) into contact with the activating composition so that a transition metal or transition metal alloy is deposited on the surface of the substrate and an activated surface for metallization is obtained. It is resolved by methods including those mentioned above.

[0028] Experiments conducted by the inventors themselves demonstrated that the present invention achieves extremely simple and effective activation without even the need for advanced stabilization / antioxidation of the formed particles. In contrast to conventional activation compositions, it was found that no stabilization / antioxidation of the formed particles is required at all. This means that in the present invention, the particles are not formed with the goal of maintaining them as much as possible, but rather to establish an equilibrium state between the dissolved transition metal ions and each particle, allowing the particles to intentionally / deliberately reform each of their ions repeatedly through oxidation. Typically, in conventional activation compositions, oxidation is considered harmful and therefore minimized and / or suppressed. In contrast, in the present invention, oxidation is considered advantageously utilized, necessary, and highly beneficial. Contrary to common views, it was found that it is not necessary to maintain the particles over a long period of time in each activation composition.

[0029] This offers numerous advantages. For example, each activated composition can be easily set up / activated in a very simple manner by simply adding the required reducing agent at the site where it is needed. This means that the delivery time of the product is independent of the lifespan of the product / method.

[0030] This invention relies on the repeated in situ formation of particles, thereby eliminating the need for any stabilizing agents or stabilizer compounds. For this reason, the dissolved transition metal ions and their metal particles exist in a reversible equilibrium state. As a result, highly effective and strong activation can be achieved because relatively short-lived, fresh particles are formed without a stabilizer compound shell. The particles then revert to their ionic form through oxidation. Further addition of a reducing agent leads to the formation of fresh particles again, i.e., in situ.

[0031] In the method of the present invention, a transition metal or transition metal alloy is deposited on the surface of the substrate, thereby obtaining an activated surface for subsequent metallization. This means that the concentration of dissolved metal ions of the first species decreases over time due to deposition. However, replenishment of the first species is easily achieved by simply adding ions of that species. Therefore, replenishment is extremely easy and convenient. This further greatly extends the lifespan of each activation composition and the associated method.

[0032] Furthermore, each method and activation composition does not necessarily require expensive precious metals, and can be carried out using inexpensive transition metals.

[0033] Furthermore, by using the rinsing step (Ia), the reliability of the entire process can be improved, and as a result, the failure rate of poorly formed copper-to-copper interconnects can be reduced. In particular, the method of the present invention provides very good and stable performance in a standard solder impact test at 288°C.

[0034] Furthermore, when using the method of the present invention, the solder impact test at 326°C was also passed with a remarkably low defect rate. This ensures higher reliability of the formed interconnects even under high thermal stress conditions.

[0035] In addition, reliability was significantly improved while maintaining or improving the coating condition and adhesion of the deposited metal layer. This avoids quality problems in the manufacturing process.

[0036] Furthermore, the additional steps do not interfere with subsequent processes and are environmentally friendly. Therefore, improvements are achieved without inserting any environmentally unfriendly methods. [Modes for carrying out the invention]

[0037] In the context of the present invention, “continuous,” “continuously,” and “sequentially” mean, respectively, that each action occurs continuously without significant interruption while, for example, each method or embodiment of the present invention is being performed.

[0038] In the context of the present invention, “semi-continuous,” “semi-continuously,” and “semi-continuously” mean, respectively, that while each method or embodiment of the present invention is being performed, each action occurs with one or more interruptions, or even significant interruptions, of the action. These interruptions may, in some cases, be longer than the duration of the action. This includes even merely temporary, short-duration actions.

[0039] In the context of this invention, "species" (e.g., first species or second species) means a chemical element. Therefore, "dissolved transition metal ion of the first species" means a dissolved metal ion of a transition metal element from Group 3 to Group 12 of the periodic table, such as copper.

[0040] In the context of the present invention, "dissolved transition metal ions of the first species and additionally the metal particles thereof" means, for example, the dissolved metal ions of the first species and additionally the metal particles thereof in a palladium-free aqueous activated composition.

[0041] Base material: In step (I)(a) of the method of the present invention, a non-conductive substrate having a surface or a carbon fiber-containing substrate is provided. Such substrates are inherently incapable of good metallization and therefore require activation.

[0042] The substrate may also include through-hole vias (THVs) and / or blind microvias (BMVs) within a non-conductive substrate or a carbon fiber-containing substrate. Here, the surface of the substrate includes the surfaces of the through-hole vias (THVs) and blind microvias (BMVs). The substrate may further include a metallic inner layer. The surfaces of the through-hole vias (THVs) and / or blind microvias (BMVs) may further include conductive regions, preferably metallic regions, and more preferably copper regions. These regions are obtained from a metallic inner layer, preferably a copper layer, within the non-conductive substrate or the carbon fiber-containing substrate.

[0043] In the context of the present invention, activation means modifying the surface of a non-conductive substrate or a carbon fiber-containing substrate in such a manner that, after each activation step, it contains a transition metal or a transition metal alloy with sufficient adhesion for subsequent metallization. Furthermore, the deposited transition metal and transition metal alloy are each sufficiently adhered to the surface, so that the subsequent metallized layer (i) can be deposited thereon, and (ii) as a whole is also sufficiently adhered to the surface of the non-conductive substrate or the carbon fiber-containing substrate.

[0044] The method of the present invention is preferable in which the non-conductive substrate is preferably selected from the group consisting of plastics, resin-containing laminates, glass, ceramics, semiconductors, and mixtures thereof.

[0045] Preferred plastics include, preferably thermoplastic plastics, and more preferably polyacrylates, polyamides, polyimides, polyesters, polycarbonates, polyalkylenes, polyphenylenes, polystyrenes, polyvinyls, or mixtures thereof.

[0046] Preferred polyacrylates include poly(methyl methacrylate) (PMMA).

[0047] Preferred polyimides include polyetherimides (PEI).

[0048] Preferred polyesters include polylactic acid (PLA).

[0049] Preferred polycarbonates include polycarbonates (PC) obtained using bisphenol A.

[0050] Preferred polyalkylenes include polyethylene (PE), polypropylene (PP), polytetrafluoroethylene (PTFE), polyoxymethylene (POM), or mixtures thereof.

[0051] Preferred polyphenylenes include poly(phenylene oxide) (PPO), poly(phenylene ether) (PPE), or mixtures thereof.

[0052] Preferred polystyrenes include polystyrene (PS), acrylonitrile butadiene styrene (ABS), styrene / butadiene rubber (SBR), and styrene-acrylonitrile (SAN).

[0053] Preferred polyvinyls include polyvinyl chloride (PVC), poly(ethylene-vinyl acetate) (PEVA), polyvinylidene fluoride (PVDF), or mixtures thereof.

[0054] Preferred resin-containing laminates include fiber-reinforced resin-containing laminates, most preferably glass fiber-reinforced laminates, and these are preferred.

[0055] More preferably, the resin-containing laminate contains one or more polymers of epoxy, vinyl ester, polyester, amide, imide, phenol, alkylene, sulfone, or mixtures thereof as the resin, most preferably one or more polymers of epoxy, imide, or mixtures thereof.

[0056] A highly preferred resin-containing laminate contains FR4, and is preferably FR4.

[0057] Preferred glass includes, and preferably includes, silica glass, soda-lime glass, float glass, fluoride glass, aluminosilicate glass, phosphate glass, borate glass, borosilicate glass, chalcogenide glass, aluminum oxide glass, or mixtures thereof.

[0058] Preferred ceramics include, and are preferably, glass ceramics, aluminum oxide ceramics, or mixtures thereof.

[0059] Preferred semiconductors include silicon-based semiconductors, more preferably silicon dioxide and / or silicon-based semiconductors containing silicon.

[0060] A highly preferred semiconductor is the wafer.

[0061] The method of the present invention is preferred in which the carbon fiber-containing substrate comprises a carbon fiber composite and / or an arrangement of carbon fiber filaments, preferably a carbon fiber composite and / or an arrangement of carbon fiber filaments.

[0062] Preferred carbon fiber composites include, and more preferably, carbon fiber reinforced polymers and / or carbon fiber-containing fabrics.

[0063] Preferred arrangements of carbon fiber filaments include, most preferably, fabrics made from carbon fibers, and most preferably, woven fabrics made from carbon fibers.

[0064] A particularly preferred carbon fiber-containing substrate is carbon fiber-containing felt.

[0065] (I) Conditioning (alternative term: pretreatment): The method of the present invention is preferable in which the conditioning solution has an alkaline pH, preferably in the range of 9.0 to 14.0, more preferably in the range of 10.0 to 13.5, even more preferably in the range of 10.5 to 13.0, and most preferably in the range of 11.0 to 12.5.

[0066] The present invention is preferable in which the nitrogen-containing compound in the conditioning solution is a polymer, preferably a water-soluble polymer.

[0067] The present invention is more preferable in which the nitrogen-containing compound in the conditioning solution is a polymer containing a pyrrolidine moiety.

[0068] Preferably, the polymer is cationic.

[0069] Preferably, the nitrogen-containing compound consists of carbon atoms, nitrogen atoms, and hydrogen atoms.

[0070] The method of the present invention is preferred in which the nitrogen-containing compound in the conditioning solution contains quaternary nitrogen atoms.

[0071] The method of the present invention is most preferable in which the nitrogen-containing compound contains polyquaternium 6, and preferably polyquaternium 6.

[0072] Another preferred method of the present invention is one in which the nitrogen-containing compound comprises, preferably, a polymer resulting from the polyaddition and / or polycondensation of at least one nitrogen-containing compound. Examples include polyamides such as nylon 6, nylon 6,6, and nylon 6,16, and polyurethanes. The most preferred method of the present invention is one in which the nitrogen-containing compound comprises, preferably, a polymer of methylamine and epichlorohydrin.

[0073] The method of the present invention is preferred in which the concentration of the nitrogen-containing compound is 0.1 g / L to 4 g / L, preferably 0.2 g / L to 2 g / L, more preferably 0.25 g / L to 1.5 g / L, and more preferably 0.3 g / L to 1 g / L.

[0074] The method of the present invention is preferable in which the conditioning solution has a temperature in the range of 20°C to 90°C, preferably in the range of 25°C to 80°C, more preferably in the range of 30°C to 70°C, and most preferably in the range of 40°C to 60°C during step (I)(c).

[0075] The present invention is preferable in which step (I)(c) is performed for 1 to 10 minutes, preferably 2 to 8 minutes, more preferably 3 to 6 minutes, and most preferably 3.5 to 5 minutes.

[0076] (Ia) Rinsing the conditioned surface Step (Ia) of the method of the present invention is a step of rinsing the surface of a non-conductive substrate or a carbon fiber-containing substrate, and the rinsing method is (a) A step of preparing the substrate processed according to step (I), (b) A step of preparing an aqueous acidic rinse composition, and (c) A step of bringing the substrate into contact with the aqueous acidic rinsing composition to obtain a rinsed surface. This process includes [the following].

[0077] The rinsing step following the conditioning step supports the subsequent selective agent treatment step. While not strictly theoretical, the rinsing step gently attacks the conditioning agent film without removing it, but this attack can improve the removal of the conditioning agent film from, for example, the inner layers of the metal substrate. The conditioning agent film is not removed from the surface of non-conductive substrates or carbon fiber-containing substrates. In this way, the quality of the copper-to-copper interconnects between the inner layers of the metal is improved. The rinsing step also improves the stability of the solder impact test results.

[0078] Furthermore, we were able to demonstrate that using a rinsing step after the selective agent treatment step deteriorates the coating condition of the substrate layer, resulting in a worsening of the backlight test results.

[0079] The method of the present invention is preferred in which the aqueous acidic rinse composition contains or consists of water and sulfuric acid. More preferably, the aqueous acidic rinse composition does not contain other mineral acids or organic acids or their salts. Experiments by the inventors themselves have shown that other mineral acids or organic acids or their salts are either non-functional or introduce inorganic anions that interfere with the subsequent steps of the method, resulting in unsatisfactory results in solder impact tests and / or backlight tests.

[0080] The method of the present invention is preferable in which the aqueous acidic rinsing composition has a pH of 1 to 6, preferably 2 to 4.5, more preferably 2.5 to 4, and most preferably 2.5.

[0081] In the present invention, the step (Ia)(c) of contacting the substrate with the aqueous acidic rinsing composition is preferably performed for 0.5 to 2 minutes.

[0082] (II) Selective treatment (alternative name: pretreatment): Step (II) of the method of the present invention is a selective agent treatment of the surface of a non-conductive substrate or a carbon fiber-containing substrate, wherein the selective agent treatment method is (a) A step of preparing the substrate processed according to step (Ia), (b) (i) Contains nitrogen-containing compounds, (ii) Having a pH of 9-14, A step of preparing a selective agent composition, and (c) A step of bringing the substrate into contact with the selective agent composition. This process includes [the following].

[0083] The method of the present invention is preferable in which the selective agent composition has an alkaline pH, preferably in the range of 9.0 to 14.0, more preferably in the range of 10.0 to 13.5, even more preferably in the range of 10.5 to 13.0, and most preferably in the range of 11.0 to 12.5.

[0084] The nitrogen-containing compound in the selective agent composition is, NH x [(CH2)n OH] 3-x (In the formula, x = 0, 1, 2, or 3, (n = 1, 2, 3, or 4) The present invention method using an amine is preferred.

[0085] The present invention is more preferable in which the nitrogen-containing compound in the selective agent composition is selected from ammonia, monoethanolamine, triethanolamine, guanidine, guanidine derivatives, such as guanidinium salts, or mixtures thereof. In the context of the present invention, "guanidine derivative" is understood as a guanidine compound, which is preferably a guanidine compound in which one or more hydrogens in guanidine are substituted with a functional group, preferably a guanidine compound substituted with a functional group such as hydroxy, halogen, amino, or C1-C4 alkyl, and / or these guanidine compounds are understood as guanidine compounds selected from guanidinium salts.

[0086] The method of the present invention is preferred in which the concentration of the nitrogen-containing compound in the selective agent composition is 1 g / L to 50 g / L, preferably 2 g / L to 40 g / L, more preferably 3 g / L to 35 g / L, and more preferably 5 g / L to 30 g / L.

[0087] Selective agent composition, (i) a) A first nitrogen-containing compound selected from ammonia, monoethanolamine, triethanolamine, or a mixture thereof, and b) A second nitrogen-containing compound selected from guanidine, guanidine compounds, such as guanidinium salts, or mixtures thereof. Includes, (ii) Having a pH of 9-12, The method of the present invention is even more preferable.

[0088] Selective agent composition, (i) a) A first nitrogen-containing compound selected from ammonia, monoethanolamine, triethanolamine, or a mixture thereof, and b) A second nitrogen-containing compound selected from guanidine, guanidine compounds, such as guanidinium salts, or mixtures thereof. Includes, (ii) Having a pH of 9-12, It is a composition, The concentration of the first nitrogen-containing compound in the selective agent composition is 1 g / L to 50 g / L, preferably 2 g / L to 40 g / L, more preferably 3 g / L to 35 g / L, and more preferably 5 g / L to 30 g / L. The concentration of the second nitrogen-containing compound in the selective agent composition is 1 g / L to 10 g / L, preferably 2 g / L to 8 g / L, more preferably 3 g / L to 7 g / L, and more preferably 4 g / L to 6 g / L. A selective agent composition is preferred.

[0089] (i) a) A first nitrogen-containing compound selected from ammonia, monoethanolamine, triethanolamine, or a mixture thereof, and b) A second nitrogen-containing compound selected from guanidine, guanidine compounds, such as guanidinium salts, or mixtures thereof. Includes, (ii) Having a pH of 9-12, It is a selective agent composition, The concentration of the first nitrogen-containing compound in the selective agent composition is 1 g / L to 50 g / L, preferably 2 g / L to 40 g / L, more preferably 3 g / L to 35 g / L, and more preferably 5 g / L to 30 g / L. The concentration of the second nitrogen-containing compound in the selective agent composition is 1 g / L to 10 g / L, preferably 2 g / L to 8 g / L, more preferably 3 g / L to 7 g / L, and more preferably 4 g / L to 6 g / L. A selective agent composition is preferred.

[0090] The method of the present invention is preferable in which the selective agent composition is at a temperature in the range of 20°C to 90°C, preferably in the range of 25°C to 80°C, more preferably in the range of 30°C to 70°C, and most preferably in the range of 40°C to 60°C during step (Il)(c).

[0091] The method of the present invention is preferable in which step (Il)(c) is carried out for 1 to 10 minutes, preferably 2 to 8 minutes, more preferably 3 to 7 minutes, even more preferably 3.5 to 6 minutes, and most preferably 4 to 5.5 minutes.

[0092] (III) Palladium-free aqueous activated composition: In step (III)(b) of the method of the present invention, a palladium-free aqueous activated composition is provided.

[0093] The aqueous composition used in the method of the present invention is an aqueous composition meaning that water is the main component. Therefore, based on the total mass of the aqueous composition, more than 50% by mass of the composition is water, preferably at least 70% by mass, more preferably at least 90% by mass, and most preferably 95% by mass or more is water. Only in rare cases is it preferable that the composition contains one or more solvents (other than water) that are miscible with water. However, it is most preferable that the composition contains only water as the solvent, and therefore most preferably substantially free of organic solvents or no organic solvents at all (for environmental protection reasons).

[0094] In the context of the present invention, the terms “substantially absent or absent” with respect to a subject substance (e.g., a compound, chemical, material, etc.) independently mean that the subject substance is either not present at all ("absent") or present only in a very small, non-interfering amount that does not affect the intended purpose of the present invention ("substantially absent"). For example, such a subject substance may be unintentionally added or utilized, for example, as an unavoidable impurity. “Substantially absent or absent” preferably means 0 ppm to 5 ppm, preferably 0 ppm to 3 ppm, more preferably 0 ppm to 1.5 ppm, even more preferably 0 ppm to 1 ppm, most preferably 0 ppm to 0.5 ppm, and most preferably 0 ppm to 0.1 ppm, based on the total mass of the activated composition. This principle also applies to other subject substances, such as the total mass of a transition metal or transition metal alloy obtained in step (III)(c) of the method of the present invention.

[0095] The activating composition has an acidic pH, a neutral pH, or an alkaline pH, preferably an acidic pH or a neutral pH, and most preferably an acidic pH.

[0096] The method of the present invention is preferable in which the pH of the activating composition is in the range of 2.0 to 13.0, preferably in the range of 3.0 to 12.0, more preferably in the range of 4.0 to 11.0, and most preferably in the range of 4.5 to 10.0.

[0097] In some cases, the method of the present invention is preferred in which the pH of the activating composition is in the range of 3.0 to 6.5, preferably in the range of 4.0 to 6.0. Preferably, this applies under the condition that one or more reducing agents contain a borohydride.

[0098] The pH of the activating composition is typically a result of the presence of (i) to (iv). If pH adjustment is necessary, it is done by typical means. Preferred acids are inorganic acids and organic acids. A preferred inorganic acid is sulfuric acid. Preferred organic acids are the acidic form of one or more complexing agents. Preferred alkali compounds are alkali hydroxides, preferably NaOH, alkali carbonates, preferably sodium carbonate, and ammonia.

[0099] In the context of this invention, pH is determined at a temperature of 20°C; that is, the specified pH is relative to 20°C. Therefore, solely for the purpose of pH determination, the activated composition has a temperature of 20°C. This does not mean that the activated composition itself is limited to a specific temperature of 20°C. For preferred temperatures of the activated composition, please refer to the following.

[0100] If the pH is significantly lower than 2 or higher than 13, little to no activation will be achieved. If the pH is excessively acidic, acid-sensitive reducing agents will typically decompose too quickly. Conversely, if the pH is excessively alkaline, alkali-sensitive reducing agents will decompose too quickly.

[0101] The aqueous compositions used in the method of the present invention are palladium-free. Therefore, the activating compositions are substantially free of palladium ions, or even completely free. This means that neither palladium-containing compounds, nor palladium atoms / particles, nor palladium ions are present. Advantageously, the present invention is a very good alternative to palladium-containing activation processes, yielding identical or at least nearly identical results in terms of activation.

[0102] Preferably, other precious metals or at least expensive / rare metals are not required in the activation composition. Therefore, the method of the present invention is preferred in which the activation composition is substantially free of or free of platinum ions, gold ions, silver ions, rhodium ions, ruthenium ions, and iridium ions, preferably substantially free of or free of platinum, gold, silver, rhodium, ruthenium, and iridium.

[0103] The aqueous composition used in the method of the present invention comprises (i) a dissolved transition metal ion of a first kind and, additionally, metal particles thereof.

[0104] The activation composition is preferably one in which the metal particles are nanoparticles. Preferably, the metal particles are one or more elemental metals (Me 0 ) contains preferably one or more elemental metals (Me 0 ) consists of (essentially).

[0105] An activation composition is even more preferable in which the first type of metal particles have a particle size in the range of 0.1 nm to 500 nm, preferably in the range of 0.5 nm to 200 nm, more preferably in the range of 1.0 nm to 100 nm, most preferably in the range of 3 nm to 50 nm, and even more preferably in the range of 5 nm to 15 nm.

[0106] The present invention is more preferable in which the first type of metal particles in the activating composition are colloidal metal particles.

[0107] Therefore, the method of the present invention is preferred in which the activating composition is colloidal, preferably a colloidal suspension. However, the activating composition is still a clear but colored solution, depending on the coloring effect mainly caused by the dissolved ions of the first type.

[0108] In the activating composition, the dissolved transition metal ions of the first species and the metal particles thereof together form the total amount of the first species of metal. The method of the present invention is preferred such that, in the activating composition, the first species of metal ions and the metal particles thereof form a total concentration in the range of 0.05 g / L to 30.0 g / L, preferably in the range of 0.07 g / L to 18.0 g / L, more preferably in the range of 0.09 g / L to 12.0 g / L, even more preferably in the range of 0.11 g / L to 8.0 g / L, most preferably in the range of 0.15 g / L to 6.0 g / L, and most preferably in the range of 0.2 g / L to 3.0 g / L, based on the total volume of the activating composition and based on the ionic non-particular form. This means that, in order to determine the total concentration, the transition metal particles of the first species are considered / calculated as dissolved metal ions.

[0109] The method of the present invention may be carried out with a first species at a relatively high concentration, but surprisingly, it has been found that even at very low concentrations, it is sufficient to obtain very efficient and excellent results (see example). This is particularly advantageous in terms of wastewater treatment, and therefore low cost and environmental friendliness.

[0110] The method of the present invention is preferred in which the first species is copper or cobalt, preferably copper. Copper and cobalt are more economical metals than commonly used palladium, but they achieve sufficient activation on the surface of non-conductive substrates or carbon fiber-containing substrates. The concentrations mentioned above are most preferably for copper and cobalt, and most preferably for copper.

[0111] The present invention is preferred in which the source of dissolved copper ions is selected from the group consisting of copper sulfate, copper chloride, copper nitrate, copper fluoroborate, copper acetate, copper citrate, copper phenylsulfonate, copper p-toluenesulfonate, and copper alkylsulfonate. The preferred copper alkylsulfonate is copper methanesulfonate. The most preferred copper source is copper sulfate, most preferably CuSO4 · It is 5H2O.

[0112] Optionally, the palladium-free aqueous activated composition contains (iv) one or more dissolved metal ions of a second species different from the first species. Preferably, the second species is substantially free of alkali metals or does not contain alkali metals at all.

[0113] The method of the present invention is preferable in which one or more second species are selected from the group consisting of transition metals and magnesium, preferably from the group consisting of nickel, cobalt, iron, and magnesium, preferably from the group consisting of nickel and cobalt, and more preferably from nickel. The corresponding transition metal alloy is deposited by the dissolved metal ions of the second species, preferably in step (c) of the method of the present invention.

[0114] The method of the present invention is preferable in which one or more second species substantially does not contain tin, or does not contain tin at all.

[0115] In addition to the first species and an optional second species, the palladium-free aqueous activated composition (ii) comprises one or more complexing agents. Preferably, one or more complexing agents are suitable for forming complexes with at least the first species of dissolved transition metal ions.

[0116] The method of the present invention is preferred in which one or more complexing agents include or comprise one or more organic complexing agents, preferably carboxylic acids and / or salts thereof, more preferably di or tricarboxylic acids and / or salts thereof, even more preferably tricarboxylic acids and / or salts thereof, most preferably hydroxytricarboxylic acids and / or salts thereof, and most preferably citric acid, its structural isomers, and / or salts thereof. Preferred structural isomers are isocitrate and its salts. Most preferably, one or more complexing agents as defined above (including preferred variations) are the only complexing agents in the activating composition.

[0117] In the activating composition, - Based on the total volume of the activating composition and based on the ionic non-specific form, a first type of metal ion and its metal particles together constitute a total concentration, - The total concentration of one or more complexing agents, The method of the present invention is preferred in which the molar ratio is within the range of 1.0:0.2 to 1.0:100.0, preferably within the range of 1.0:0.5 to 1.0:50.0, more preferably within the range of 1.0:0.85 to 1.0:25.0, even more preferably within the range of 1.0:0.95 to 1.0:15.0, even more preferably within the range of 1.0:1.0 to 1.0:10.0, and most preferably within the range of 1.0:1.1 to 1.0:5.0. This is especially preferred when one or more complexing agents include tricarboxylic acid and / or a salt thereof, more preferably hydroxytricarboxylic acid and / or a salt thereof, most preferably citric acid, its structural isomers, and / or a salt thereof.

[0118] The method of the present invention is preferable in which one or more complexing agents in the activating composition are present in a total amount in the range of 0.01 mol / L to 0.5 mol / L, preferably in the range of 0.015 mol / L to 0.35 mol / L, more preferably in the range of 0.02 mol / L to 0.3 mol / L, and most preferably in the range of 0.023 mol / L to 0.275 mol / L, based on the total volume of the activating composition.

[0119] In addition to a first species, optionally a second species, and one or more complexing agents, the palladium-free aqueous activated composition permanently or temporarily contains (iii) one or more reducing agents. One or more reducing agents are essential for forming metal particles from dissolved transition metal ions of at least the first species. For this purpose, the dissolved transition metal ions are chemically reduced continuously or semi-continuously to form the particles. Thus, the particles are formed either continuously or semi-continuously, depending on the presence of one or more reducing agents in the activated composition, whether permanent or temporary. However, when one or more reducing agents are present, typically the particles will be formed until the reducing agents are depleted or their amount becomes insufficient. The method of the present invention is preferred in which oxidation affects the particles and is always competing with reduction. Typically, oxidation begins as soon as one or more reducing agents are depleted, which is explicitly desired in the context of the present invention.

[0120] The oxidation is particularly relevant in the method of the present invention when the method is interrupted for a relatively long period of time after one or more first steps (c). To prevent the precipitation of aggregates during such a time, the oxidation is carried out in the activated composition until no particles are present and only dissolved transition metal ions remain. Preferably, the oxidation is facilitated by adding an oxidizing agent, more preferably a peroxide, most preferably hydrogen peroxide. Upon resumption of the operation, particles are formed by continuously or semi-continuously adding one or more reducing agents to reform the particles. The method of the present invention is then resumed.

[0121] Therefore, preferably, one or more reducing agents are suitable for reducing at least the first type of dissolved transition metal ion.

[0122] In some cases, the method of the present invention is preferable in which one or more reducing agents contain one or more hydrogen atoms such that hydrogen is released when the transition metal ion is reduced and at least a portion of it is adsorbed onto the activated surface.

[0123] The method of the present invention is preferable in which one or more reducing agents include a boron-containing reducing agent, preferably a borohydride. Preferred borohydrides include inorganic borohydrides and / or organic borohydrides. Preferred organic borohydrides include alkylaminoboranes, most preferably dimethylaminoboranes. Preferred inorganic borohydrides include alkaline borohydrides, most preferably sodium borohydride. In the method of the present invention, the most preferred is an alkaline borohydride, preferably sodium borohydride. This allows for a slightly acidic pH and a mild temperature range, preferably 15°C to 30°C, in step (c) of the method of the present invention. These are excellent room temperature conditions. Therefore, additional costly heating is not necessarily required. Furthermore, hydrogen is generated.

[0124] Preferably, a boron-containing reducing agent, preferably a borohydride, more preferably an alkaline borohydride and / or alkylaminoborane, and most preferably sodium borohydride and / or dimethylaminoborane, is the sole reducing agent in the activating composition.

[0125] Typically, when a borohydride is used as one or more reducing agents in an activating composition, boric acid and / or its salts are formed.

[0126] In some cases, the method of the present invention is preferable in which one or more reducing agents include an aldehyde, preferably formaldehyde, glyoxylic acid, a salt of glyoxylic acid, or a mixture thereof, most preferably as the sole reducing agent. In such cases, the formation of boric acid is avoided.

[0127] In some cases, the method of the present invention is preferable in which one or more reducing agents are included, most preferably hydrazine as the sole reducing agent. In such cases as well, the formation of boric acid is avoided.

[0128] The method of the present invention is preferable in which the activating composition contains one or more reducing agents at a total concentration in the range of 0.2 mmol / L to 500.0 mmol / L, preferably in the range of 0.4 mmol / L to 350.0 mmol / L, more preferably in the range of 0.6 mmol / L to 250.0 mmol / L, even more preferably in the range of 0.8 mmol / L to 150.0 mmol / L, and most preferably in the range of 1.0 mmol / L to 80.0 mmol / L, based on the total volume of the activating composition. Particularly preferred total concentrations are in the range of 0.9 mmol / L to 50.0 mmol / L, very preferably in the range of 1.0 mmol / L to 30.0 mmol / L, and most preferably in the range of 1.1 mmol / L to 10.0 mmol / L. Most preferably, this applies to the preferred, more preferred, etc. reducing agents mentioned above, most preferably borohydrides.

[0129] In the activating composition, - Based on the total volume of the activating composition and based on the ionic non-specific form, a first type of metal ion and its metal particles together form a total concentration, - The total concentration of one or more reducing agents (at the moment of addition if added semi-continuously) The method of the present invention is generally preferred in which the molar ratio is greater than 0.5, preferably 1 or more, more preferably 2 or more, even more preferably 3 or more, and most preferably 3.5 or more. A molar ratio in the range of 1 to 20 is very preferred. Therefore, it is preferable that one or more reducing agents in the activating composition are present (permanently or temporarily) at a total concentration such that the dissolved transition metal ions of the first type are not quantitatively reduced to the corresponding particles. Furthermore, it is preferable that the method of the present invention does not predominantly exhibit a reducing environment that prevents oxidation of the metal particles. Conversely, as already stated, oxidation is necessary and desired. Therefore, it is preferable that the method of the present invention is predominantly maintained under oxidizing conditions that allow oxidation of the metal particles.

[0130] In the activating composition, - Based on the total volume of the activating composition and based on the ionic non-specific form, a first type of metal ion and its metal particles together form a total concentration, - The total concentration of one or more reducing agents (at the moment of addition if added semi-continuously) The method of the present invention is particularly preferred in which the molar ratio exists within the range of 0.3 to 60.0, preferably within the range of 0.5 to 30.0, more preferably within the range of 1.0 to 20.0, even more preferably within the range of 1.5 to 10.0, and most preferably within the range of 1.8 to 3.0.

[0131] In some cases, the method of the present invention is preferred in which one or more reducing agents are permanently present in the palladium-free aqueous activating composition. Therefore, it is preferable that one or more reducing agents are added to the activating composition continuously, preferably by a permanent flow of each liquid containing the one or more reducing agents. In this method, oxidation and reduction occur simultaneously over the time that step (c) of the method of the present invention is performed. As a result, metal particles are present at a relatively constant concentration.

[0132] Alternatively, the method of the present invention is preferred in which one or more reducing agents are temporarily present in the palladium-free aqueous activation composition. Therefore, preferably, one or more reducing agents are added semi-continuously, for example, in consecutive additions with time interruptions between each addition. This means that new particles are formed when one or more reducing agents are added. However, during the interruption, oxidation that generates dissolved transition metal ions is very dominant. As a result, metal particles are present at basically fluctuating concentrations. However, depending on the length of the time interruption, and by ensuring that the interruption is not too long, such a method is perfectly sufficient to successfully activate the surface of multiple non-conductive substrates or carbon fiber-containing substrates. Therefore, this method is particularly preferred.

[0133] However, in any case, the method of the present invention is preferred in which one or more reducing agents are present in such a way that the equilibrium is reversibly maintained. Therefore, the reversible equilibrium is not merely a side reaction or an undesirable side reaction.

[0134] During oxidation, the total concentration of dissolved transition metal ions in the activating composition increases, essentially as a result of reversible equilibrium, while the total amount of metal particles decreases. This reversible equilibrium is preferably monitored for better process control. Therefore, the method of the present invention in which the reversible equilibrium is monitored by UV / VIS inspection is preferred. Preferably, the dissolved transition metal ions are monitored at wavelengths in the range of 700 nm to 800 nm, 710 nm to 780 nm, more preferably 720 nm to 760 nm, and most preferably 730 nm to 750 nm. It is also preferable that the metal particles are monitored at wavelengths in the range of 400 nm to 600 nm, preferably 450 nm to 550 nm. This allows for determining the timing of adding one or more reducing agents for the purpose of forming, preferably reforming, the metal particles to increase their total amount.

[0135] Therefore, the method of the present invention is preferred in which one or more reducing agents are added to the activating composition continuously or semi-continuously, preferably after one or more steps (c) have been performed, so that further metal particles are formed continuously or semi-continuously from the dissolved transition metal ions of the first type.

[0136] The method of the present invention is preferred in which metal particles of a first type are formed in situ, continuously or semi-continuously, in the activated composition by reduction after and / or during one or more steps (c) have been performed. Preferably, in the method of the present invention, it is defined that step (c) is performed two or more times, preferably that the method comprising step (c) is repeated. It is very preferred that new metal particles are formed by reduction after one step (c), two or more steps (c), or after each step (c) of the method of the present invention. This is possible because the oxidation is possible and desired, thereby yielding new dissolved transition metal ions that are immediately re-reduced, continuously but preferably semi-continuously. This is in contrast to the common practice in which metal particles are formed (and stabilized) before activation takes place, and the metal particles then persist for as long as possible by particle stabilization, typically until the corresponding activated composition becomes destabilized and unusable.

[0137] As mentioned throughout this text, in the context of the present invention, it is preferably necessary to add the reducing agent at least semi-continuously. Typically, the reducing agent used for the reduction reacts with dissolved transition metal ions to yield reducing agent decomposition products, preferably boric acid and / or salts thereof. Such decomposition products usually accumulate in the activating composition, which is undesirable in the context of the present invention. Therefore, the method of the present invention, in which the method is carried out by bleed and feed, is preferred. In such a method, a certain volume of the activating composition is removed (e.g., by abstraction; which also removes the decomposition products) and replaced by a substituted volume (e.g., by replenishment) so that the essential components in the activating composition are at a sufficiently constant concentration. This means that the substituted volume typically does not contain boric acid and / or salts thereof, preferably does not contain reducing agent decomposition products. This is also beneficial for stabilizing the pH to a essentially constant pH.

[0138] The method of the present invention is preferable in which the activating composition comprises boric acid and / or its salts with a total concentration of 5 g / L or less, preferably 3 g / L or less, more preferably 2 g / L or less, and most preferably 1.2 g / L or less, based on the total volume of the activating composition. This is preferably the case under the conditions that (1) one or more reducing agents contain borohydrides, and (2) step (c) is performed two or more times.

[0139] The method of the present invention is preferred in which the reversible equilibrium does not shift predominantly towards the metal particles for most of the time during which process (c) is performed.

[0140] The present invention is preferred in which the majority of the metal particles undergo the oxidation during and / or after step (c). "Majority" preferably means more than 50% of the particles.

[0141] Preferably, one or more reducing agents are substantially free of hypophosphate ions, and preferably substantially free of phosphorus-containing reducing agents. Experiments by the inventors themselves have shown that, in some cases, activation by such reducing agents is too weak or even incomplete.

[0142] As outlined above, the activating composition does not require additional stabilizing compounds. Therefore, a method of the present invention is preferable in which the activating composition substantially does not contain or contains no compounds that prevent oxidation of metal particles and / or substantially does not contain stabilizing compounds for stabilizing metal particles. Preferably, the activating composition substantially does not contain or contains no stabilizing compounds for stabilizing metal particles by preventing aggregation of metal particles. In the context of the present invention, one or more reducing agents (temporarily or permanently present in the activating composition) and compounds involved in oxidation, preferably ambient air and / or oxygen gas (i.e., most preferably molecular oxygen) are not considered such compounds. One or more reducing agents are rather necessary for the formation of metal particles, including particle reformation. This means that the activating composition substantially does not contain or contains stabilizing compounds and / or compounds that prevent oxidation of metal particles, other than the one or more reducing agents and compounds involved in oxidation. Therefore, the method of the present invention is preferable in which one or more reducing agents are not present in a total amount sufficient to prevent oxidation, preferably not in a total amount sufficient to prevent oxidation after or during one or more steps (c) are performed. As outlined, oxidation, most preferably by ambient air, is necessary to prevent the formation of aggregates of the precipitated metal particles by reforming the dissolved transition metal ions.

[0143] The method of the present invention is preferable in which the activating composition substantially does not contain compounds that completely or partially encapsulate metal particles, or compounds that completely or partially adsorb onto the surface of the particles. Some stabilizer compounds are thought to be based on such functions. In the context of the present invention, this is undesirable.

[0144] Generally, the method of the present invention is preferred in which the activating composition substantially does not contain any compounds that prevent the equilibrium from becoming reversible, and / or substantially does not contain any compounds that cause the equilibrium to shift completely to the side of the metal particles. Here again, for the reasons outlined above, one or more reducing agents are not considered to be such compounds.

[0145] The method of the present invention is preferred in which the activation composition is substantially free of or free of tin ions, preferably substantially free of tin ions, lead ions, germanium ions, gallium ions, antimony ions, bismuth ions, and aluminum ions, and more preferably substantially free of or free of metal ions of the main group elements of Groups III, IV, and V of the periodic table. In the context of the present invention, "metal ions of the main group elements of Group III" does not include the corresponding boron-containing ions. In particular, tin ions are very well known to prevent, for example, the oxidation of copper particles in the corresponding palladium-free copper-tin activation composition, thereby preventing the equilibrium from becoming reversible. Such tin ions typically form a reducing environment, which is completely undesirable in the context of the present invention.

[0146] The method of the present invention is preferable in which the activating composition substantially does not contain polyvinylpyrrolidone, preferably substantially does not contain polyvinyl compounds, more preferably substantially does not contain organic polymers containing a vinyl portion, and most preferably substantially does not contain dissolved organic polymers.

[0147] The method of the present invention is preferable in which the activating composition is substantially free of or does not contain proteins, agar, gum arabic, sugars, and polyhydric alcohols.

[0148] The method of the present invention is preferable in which the activating composition is substantially free of or free of glycerol.

[0149] The method of the present invention is preferable in which the activating composition is substantially free of gelatin or does not contain gelatin.

[0150] The method of the present invention is preferable in which the activating composition substantially does not contain thiourea, preferably substantially does not contain sulfur-containing compounds containing divalent sulfur, and more preferably substantially does not contain sulfur-containing compounds containing sulfur with an oxidation state of +5 or less.

[0151] The method of the present invention is preferable in which the activating composition substantially does not contain or does not contain compounds containing aromatic rings and sulfonic acid groups (including salts thereof), preferably substantially does not contain or does not contain sulfonic acid or salts thereof.

[0152] The method of the present invention is preferable in which the activating composition substantially does not contain or does not contain the compound named Orzan-S.

[0153] The method of the present invention is preferable in which the activating composition is substantially free of or free of urea.

[0154] The method of the present invention is preferable in which the activating composition is substantially free of or free of a dispersant.

[0155] The method of the present invention is preferable in which the activating composition substantially does not contain polyethyleneimine, preferably substantially does not contain polyalkyleneimine, and most preferably substantially does not contain an organic polymer containing an imine moiety.

[0156] In particular, the polymers mentioned above are commonly used as stabilizer compounds to stabilize metal particles. However, in the context of the present invention, polymers are not necessary. Furthermore, metal particles are considered to be significantly more effective / more active when such molecules do not form a shell around the particles.

[0157] The method of the present invention is preferable in which the activating composition substantially does not contain sodium dodecyl sulfate, preferably substantially does not contain alkyl sulfates having 8 to 20 carbon atoms, more preferably substantially does not contain alkyl sulfates, and most preferably substantially does not contain surfactants.

[0158] The method of the present invention is preferable in which the activating composition is substantially free of hydroquinone, pyrogallol, and / or resorcinol, and more preferably substantially free of hydroxybenzene. In many cases, such hydroxybenzene is commonly used as an antioxidant and prevents the equilibrium from becoming reversible, so it is unnecessary in the activating composition.

[0159] The method of the present invention is preferable in which the activating composition is substantially free of or free of quinone.

[0160] The method of the present invention is preferable in which the activating composition is substantially free of fatty alcohols or does not contain any fatty alcohols.

[0161] The method of the present invention is preferable in which the activating composition is substantially free of alkylene glycol, preferably substantially free of glycol.

[0162] The method of the present invention is preferable in which the activating composition is substantially free of or does not contain manganese ions.

[0163] The method of the present invention is preferable in which the activating composition is substantially free of or free of zinc ions.

[0164] As a result of the activation composition not containing stabilizing compounds and / or compounds that prevent oxidation of metal particles, it is preferable, in particular despite such fact, that the method of the present invention substantially does not contain aggregates of precipitated metal particles. This is achieved because oxidation is not suppressed (i.e., avoided), but rather at least the dissolved transition metal ions of the first species and their metal particles repeatedly participate in the reduction and oxidation, respectively.

[0165] The method of the present invention is preferred, where "repeated involvement" explicitly includes at least two, preferably three, more preferably four, most preferably five, and most preferably the entire lifespan of the activating composition.

[0166] Experiments by the inventors themselves have shown that oxidation, in particular, prevents aggregation. Metal particles revert to their ionic / dissolved form through oxidation. This means that there is not enough time for the particles to form higher-order aggregates, and even more so, aggregates. While each of the suitable oxidizing agents is essentially applicable, ambient air has been shown to be a very good choice. It is sufficiently strong and available everywhere. The method of the present invention is preferred in which the formation of precipitated aggregates of the metal particles is prevented by oxidation, preferably by oxidation with ambient air and / or oxygen gas. The method of the present invention is preferred in which dissolved transition metal ions are formed from the metal particles by oxidation with ambient air and / or oxygen gas. In either case, the preferred oxidizing agent is molecular oxygen. The method of the present invention is most preferred in which the majority of dissolved transition metal ions are formed from the majority of the metal particles by oxidation with ambient air and / or oxygen gas.

[0167] In some cases, the method of the present invention is preferred in which continuous or semi-continuous oxidation is achieved, either additionally or alone, by an oxidizing agent other than molecular oxygen, more preferably by a peroxide, most preferably by hydrogen peroxide. In particular, in addition to ambient air, this is preferred when it is required, for example, when the activated composition needs to be deactivated and stored for a long period of time.

[0168] In order to sufficiently promote oxidation in the activated composition, the method of the present invention is preferred in which the activated composition is continuously or semi-continuously circulated, preferably by shaking, stirring, and / or pumping. This is preferred in order to ensure that oxidation is evenly distributed throughout the activated composition. In other words, this ensures that the metal particles come into even contact with the oxidizing agent and that oxidation is promoted.

[0169] The present invention is a method for producing a palladium-free aqueous activating composition (preferably the activating composition used in the present invention) for activating the surface of a non-conductive substrate or a carbon fiber-containing substrate for metallization, (1) - Dissolved transition metal ions of the first species, and - One or more complexing agents, and - Optionally, one or more dissolved metal ions of a second species different from the first species. A step of preparing a starting aqueous solution containing, (2) A step of continuously or semi-continuously adding one or more reducing agents to the starting solution such that metal particles of at least the first type of dissolved transition metal ion are continuously or semi-continuously formed in the solution. This includes, however, The metal particles are continuously or semi-continuously oxidized to form a first type of dissolved transition metal ion, and are used to provide a palladium-free aqueous activated composition according to the method of the present invention. Use the method.

[0170] In other words, the method of the present invention for producing a palladium-free aqueous activating composition for activating the surface of a non-conductive substrate or a carbon fiber-containing substrate is used to provide a palladium-free aqueous activating composition used in the present invention.

[0171] The manufacturing method of the present invention also relates to the use of a combination of continuous or semi-continuous reduction of a first species of dissolved transition metal ion and continuous or semi-continuous oxidation of the first species of metal particles in a reversible equilibrium state for continuously or semi-continuously forming metal particles in situ in a palladium-free aqueous activated composition used in a method for treating the surface of a non-conductive substrate or a carbon fiber-containing substrate according to the present invention.

[0172] Preferably, the activating composition used in the method of the present invention is obtained and / or has a temperature in the range of 10°C to 90°C, preferably in the range of 14°C to 75°C, more preferably in the range of 16°C to 65°C, most preferably in the range of 18°C ​​to 45°C, and even more preferably in the range of 20°C to 32°C. In particular, the temperature is preferably in the range of 18°C ​​to 45°C, preferably in the range of 20°C to 32°C, wherein one or more reducing agents are borohydrides, preferably sodium borohydride. This also particularly applies to the method for producing the activating composition used in the method of the present invention.

[0173] More preferably, the activating composition used in the present invention is not obtained at temperatures above 110°C, preferably above 100°C, more preferably above 95°C, and / or does not have these temperatures. Most preferably, the activating composition of the present invention is not obtained at temperatures above 110°C. This also preferably applies to the method for producing the activating composition used in the method of the present invention.

[0174] Activation (Step (III)): In step (III)(c) of the method of the present invention, the substrate is brought into contact with a palladium-free aqueous activating composition in order to obtain an activated surface for metallization by depositing a metal or metal alloy, that is, by depositing a seed layer or an activated layer.

[0175] In step (III)(c), the method of the present invention is preferable in which the contact is carried out at a temperature in the range of 10°C to 90°C, preferably in the range of 14°C to 75°C, more preferably in the range of 16°C to 65°C, most preferably in the range of 18°C ​​to 45°C, and even more preferably in the range of 20°C to 32°C. Particularly preferred temperatures in step (III)(c) are in the range of 18°C ​​to 45°C, preferably in the range of 20°C to 32°C, and the reduction with one or more reducing agents is a borohydride, preferably sodium borohydride.

[0176] In step (III)(c), the method of the present invention is preferred in which the contact is carried out for a period of time ranging from 1 minute to 10 minutes, preferably 2 minutes to 8 minutes, more preferably 3 minutes to 6 minutes, and most preferably 3.5 minutes to 5 minutes.

[0177] The present invention is preferable in which a rinsing step is performed after step (III)(c). In such a case, a rinsed activated surface for metallization is obtained. Preferably, the rinsing is performed with water.

[0178] The preferred method of the present invention is one in which the method is carried out for 10 days or more, preferably 50 days or more, more preferably 200 days or more, even more preferably 1 year or more, most preferably 2 years or more, and most preferably 5 years or more, without replacing the majority of the activated composition (i.e., more than 50% by volume of the composition) in a single step.

[0179] Metallization: The present invention further provides a method for metallizing the activated surface of a non-conductive substrate or a carbon fiber-containing substrate, (A) A step of preparing a non-conductive substrate or a carbon fiber-containing substrate having an activated surface for metallization, preferably obtained by the method of the present invention as preferably defined as preferred throughout this document, and (B) A step of metallizing the activated surface by bringing the activated surface into contact with the first metallization solution so that the first metallized layer is deposited on the activated surface. including, Regarding the method.

[0180] In step (A) of the method (for metallization) of the present invention, the non-conductive substrate or carbon fiber-containing substrate having an activated surface is provided in the state obtained by the method of the present invention; for details, please refer to the above text. Preferably, the matters described above with respect to the method of the present invention apply to the method for metallization of the present invention, as most preferably.

[0181] In step (B), the method (for metallization) of the present invention is preferable in which the first metallized layer is another layer deposited on the transition metal or transition metal alloy obtained in step (III)(c) of the method of the present invention.

[0182] In step (B), the preferred method (for metallization) of the present invention is one in which the first metallization solution essentially does not contain or does not contain a reversible equilibrium between metal ions and their particles, more preferably essentially does not contain or does not contain metal / metal alloy particles, and most preferably essentially does not contain or does not contain any particles.

[0183] In step (B), the first metallization solution is preferably one that contains or does not contain a reducing agent, according to the present invention's method (for metallization).

[0184] The present invention's method (for metallization) is preferable in which step (B) is carried out at a temperature in the range of 10°C to 95°C, preferably in the range of 15°C to 85°C, more preferably in the range of 20°C to 65°C, even more preferably in the range of 25°C to 55°C, and most preferably in the range of 30°C to 45°C.

[0185] The present invention's method (for metallization) is preferable in which step (B) is carried out for 30 seconds to 180 minutes, preferably 45 seconds to 120 minutes, more preferably 1 minute to 60 minutes, and most preferably 1.5 minutes to 45 minutes.

[0186] In step (B), the first metallization solution is an immersion-type metallization solution that does not contain a reducing agent, and preferably contains one or more ions selected from the group consisting of palladium ions, platinum ions, silver ions, gold ions, and mercury ions, more preferably contains palladium ions, and most preferably contains palladium ions in a total concentration in the range of 0.05 mg / L to 20 mg / L, which is preferred in the present invention's (metallization) method.

[0187] In step (B), the present invention's method (for metallization) is more preferable in which the first metallization solution is an acidic palladium immersion type metallization solution.

[0188] In step (B), the preferred method (for metallization) of the present invention is an immersion-type metallization solution in which the first metallization solution contains palladium ions at a total concentration in the range of 0.09 mg / L to 10.0 mg / L, preferably 0.1 mg / L to 5.0 mg / L, more preferably 0.12 mg / L to 3.0 mg / L, even more preferably 0.15 mg / L to 2.0 mg / L, most preferably 0.2 mg / L to 1 mg / L, and most preferably 0.22 mg / L to 0.75 mg / L, based on the total volume of the metallization solution. This is especially true when the metallization solution is acidic. In combination with the method of the present invention, such a metallization solution, surprisingly, requires a much lower concentration of palladium ions compared to conventional prior art metallization solutions, but in the context of the present invention, this does not impair the results / quality of the metallization.

[0189] Alternatively, the present invention's method (for metallization) is preferable in which, in step (B), the first metallization solution is a self-catalytic metallization solution containing a reducing agent, preferably containing one or more types of transition metal ions, more preferably copper ions and / or nickel ions. Preferably, the first metallization solution in step (B) is a self-catalytic metallization solution containing copper ions and a reducing agent capable of reducing the copper ions to metallic copper.

[0190] However, the first metallization solution, regardless of its type, is preferably a transparent solution that does not contain particles.

[0191] The preferred method is the present invention (for metallization), (A) A step of preparing a non-conductive substrate or a carbon fiber-containing substrate having an activated surface for metallization, preferably obtained by the method of the present invention as preferably defined as preferred throughout this document, (B) A step of metallizing an activated surface by bringing it into contact with a first metallization solution, which is a self-catalytic metallization solution containing copper ions and a reducing agent, such that a first metallization layer containing copper or a copper alloy is deposited on the activated surface. This method includes [something].

[0192] Alternatively, the present invention (for metallization) is preferable, (A) A step of preparing a non-conductive substrate or a carbon fiber-containing substrate having an activated surface for metallization, preferably obtained by the method of the present invention as preferably defined as preferred throughout this document, (B) A step of metallizing the activated surface by bringing the activated surface into contact with a first metallization solution, which is an immersion-type metallization solution containing palladium ions (preferably as described above), such that a first metallization layer containing palladium is deposited at least partially on the activated surface, and subsequently (C) A process of metallizing the first metallized layer by bringing the first metallized layer into contact with a second metallization solution such that the second metallized layer is deposited on top of the first metallized layer. This method includes [something].

[0193] In step (C), the second metallization solution preferably contains a reducing agent, and more preferably contains a reducing agent and nickel ions, in the present invention's (method for metallization).

[0194] Therefore, in step (C), the method (for metallization) of the present invention is preferred in which the second metallized layer contains nickel, preferably a nickel layer or a nickel alloy layer.

[0195] However, in other cases, in step (C), the second metallization solution is preferably a reducing agent, preferably a reducing agent and copper ions, according to the present invention (for metallization).

[0196] Therefore, in step (C), the method (for metallization) of the present invention is preferred in which the second metallized layer contains copper, preferably a copper layer or a copper alloy layer.

[0197] In other cases, in step (C), the second metallization solution preferably contains a reducing agent, and more preferably a reducing agent and cobalt ions, according to the present invention (for metallization).

[0198] Therefore, the method (for metallization) of the present invention is preferred, wherein in step (C), the second metallized layer is a cobalt-containing, preferably cobalt layer or cobalt alloy layer.

[0199] In step (C), the method (for metallization) of the present invention is preferred such that the deposition of the second metallization layer begins within 8 to 30 seconds, preferably within 10 to 25 seconds, and most preferably within 12 to 20 seconds. This is most preferably the case when the second metallization layer contains nickel, preferably a nickel layer or a nickel alloy layer. Thus, the inventors' own experiments have shown that the first metallization layer containing palladium acts as a booster for the second metallization layer of nickel or a nickel alloy.

[0200] The present invention will be described in more detail by the following examples, which are not limited to this invention. [Examples]

[0201] Test method: Backlight test (condition of metal coating on the substrate surface): The coating condition is evaluated using an industrial standard backlight test, which separates the corresponding substrates and allows for the detection of areas with incomplete coating as bright spots when viewed under a strong light source (see U.S. Patent Publication No. 2008 / 0038450(A1) and International Publication No. 2013 / 050332). The quality of the coating is judged by the amount of light observed under a conventional optical microscope. The results are given on a scale from D1 to D10, where D1 (less incomplete coating) is the worst result and D10 (complete and strong coating) is the best result.

[0202] Peel strength: ABF test specimens that had been electroless plated were immersed in a 10% H2SO4 solution at room temperature for 10 seconds, and then electroplated with 35 μm of copper. After plating, the specimens were fully cured according to Ajinomoto's recommendations. Subsequently, the specimens were cut into 1 cm wide strips using a router machine. The force required to peel the copper thin film from these strips was measured at a peeling speed of 50.8 mm / min using an Erichsen Uni mat Plus 050-2kN material testing machine equipped with a 20 N load cell, while ensuring that the peeling angle was always 90°.

[0203] Solder impact test (SST): SST was performed at 288°C and 326°C, respectively, according to IPC standard: IPC-TM-650, No. 2.6.8, Revision E, Thermal Stress, Plating - Through Hole. After electroless copper plating, electrically reliable test specimens were immersed in a 10% H2SO4 solution at room temperature for 10 seconds, and then electroplated with 40 μm of copper. Subsequently, the test specimens were annealed at 140°C for 6 hours, cooled to room temperature, and then subjected to a solder impact test. In the solder impact test, the test specimens were floated on molten solder at 288°C or 326°C for 10 seconds, and then cooled again to room temperature. This floating and cooling procedure was repeated at least 5 to 9 times. At least 3 repeated tests were performed for each test condition, with and without a rinsing step.

[0204] Test specimen To evaluate the quality of electroless copper deposits, test specimens made of acrylonitrile butadiene styrene (ABS), FR4, and laminated Ajinomoto Build-Up Film (ABF) GX-92R were used (Table 1). The parameters tested were appearance, blistering, deposit thickness, coverage, and electrical reliability.

[0205] [Table 1]

[0206] Conditions for ABF lamination ABF GX-92R prepreg was laminated onto a copper-clad FR4 panel treated with Bondfilm® using a Dynachem VA 7124-HP6 vacuum lamination machine (lamination conditions: vacuum time 30 seconds, dynamic slap-down time 30 seconds, static slap-down time 20 seconds, vacuum setting 2.0 mbar, pressure 5.0 kg / cm²). 2 ). Subsequently, the laminated panels were partially cured in an air-circulating oven, following Ajinomoto's recommendations.

[0207] Desmia's conditions The test specimens were subjected to desmear treatment using the Securiganth® series treatment baths shown in Table 2 (this represents the so-called desmear process).

[0208] [Table 2]

[0209] (Example 1) The test specimens were processed according to the conditions detailed in Table 3.

[0210] [Table 3]

[0211] The following results were obtained. Appearance of electroless copper deposits: salmon pink, no blistering. • Sediment thickness: 1 μm • Backlight test performance: D9-D10 5x • Performance of solder impact test on 6 test specimens: Interconnection defect (ICD) (ICD 6×288℃) 1.7% (average) after 6 impacts (10 seconds each) at 288℃. • Performance of solder impact test on 4 test specimens: Interconnection defect (ICD) (ICD 9×326℃) after 9 impacts (10 seconds each) at 326℃: 23.65% (average)

[0212] (Example 2) Two test specimens were treated according to the conditions detailed in Table 3. In this treatment, the rinsing agent in step 4) contained 0.009 g / L (62% by weight) of sulfuric acid and had a pH of 4.

[0213] The following results were obtained. Appearance of electroless copper deposits: salmon pink, no blistering. • Sediment thickness: 1 μm • Solder impact test performance: Interconnection defect (ICD) (ICD 6×288℃) 2% (average) after 6 impacts (10 seconds each) at 288℃.

[0214] Comparative Example 1 (Method based on industrial palladium as a standard control) Two representative test specimens of industrially used palladium-based processes were processed according to the conditions detailed in Table 4.

[0215] [Table 4]

[0216] The following results were obtained. Appearance of electroless copper deposits: salmon pink, no blistering. • Sediment thickness: 1 μm • Backlight test performance: D9.5 • Solder impact test performance: 0% interconnection defect (ICD) after 6 impacts (10 seconds each) at 288°C.

[0217] Comparative Example 2 (Palladium-free method without a rinsing step) The test specimens were processed according to the conditions detailed in Table 3, i.e., under the same conditions as in Example 1, except that a rinsing step was omitted.

[0218] The following results were obtained. • Sediment thickness: 1 μm • Backlight test performance: D9.5 • Performance of solder impact test on 6 test specimens: Interconnection defect (ICD) (ICD 6×288℃) 4.5% (average) after 6 impacts (10 seconds each) at 288℃. • Performance of solder impact test on 4 test specimens: Interconnection defect (ICD) (ICD 9×326℃) 37% (average) after 9 impacts (10 seconds each) at 326℃.

[0219] Comparative Example 3 (Palladium-free method without selective agent treatment) Without performing step 5, which involves selective agent treatment, two test specimens were processed according to the conditions detailed in Table 3.

[0220] The following results were obtained. • Sediment thickness: 1 μm • Backlight test performance: D5.5-D6 • Solder impact test performance: Interconnection defect (ICD) (ICD 6×288℃) after 6 impacts (10 seconds each) at 288℃: 40.2% (average)

[0221] Example 4 (Effects of acidic rinsing) Further results regarding the effect of the presence or absence of an acidic rinsing process, in terms of the performance of the solder impact test at 326°C on the deposited copper layer, the coating condition, and adhesion, are shown below.

[0222] The test specimens were treated according to the conditions detailed in Table 3 above. In the examples, the specimens were treated with an acidic rinsing step using an aqueous acidic rinsing composition with a pH value of 1, 2.5, 4, or 6. The comparative examples were treated without an acidic rinsing step.

[0223] result:

[0224] [Table 5]

[0225] The backlight test showed that the examples and comparative examples exhibited comparable good coating performance, and it was possible to demonstrate that a pH value of 2.5 showed the best performance.

[0226] [Table 6]

[0227] The peel strength test showed good results in the examples, with pH values ​​of 2.5 to 6 demonstrating better performance than without the acidic rinsing step. The best performance was observed at pH 2.5 and 4.

[0228] [Table 7]

[0229] While good performance has already been demonstrated in backlight and peel strength tests, the solder impact test shows impressive improvement in all examples compared to the comparative example without the acidic rinsing process. Best performance was observed at pH 2.5 and 4.

[0230] The results further demonstrate that the method of the present invention, which uses an acidic rinsing step, not only provides excellent reliability of the formed interconnects even under high thermal stress conditions, but also maintains or further improves the coating and adhesion of the deposited metal layer.

Claims

1. A method for treating the surface of a non-conductive substrate or a carbon fiber-containing substrate, (I) A step of conditioning the surface of a non-conductive substrate or a carbon fiber-containing substrate, wherein the conditioning method is: (a) Steps to prepare the base material, (b) A step of preparing a conditioning composition containing a nitrogen-containing compound, and (c) A step of bringing the substrate into contact with the conditioning composition to obtain a conditioned surface. Processes including (Ia) A step of rinsing the surface of a non-conductive substrate or a carbon fiber-containing substrate, wherein the rinsing method is (a) A step of preparing the substrate processed according to step (I), (b) A step of preparing an aqueous acidic rinse composition, and (c) A step of bringing the substrate into contact with the aqueous acidic rinsing composition to obtain a rinsed surface. Processes including (II) A step of selective agent treatment of the surface of a non-conductive substrate or a carbon fiber-containing substrate, wherein the selective agent treatment method is (a) A step of preparing the substrate processed according to step (Ia), (b) (i) Contains nitrogen-containing compounds, (ii) Having a pH of 9 to 14, A step of preparing a selective agent composition, and (c) A step of bringing the substrate into contact with the selective agent composition. Processes including, and (III) A step of activating the surface of a non-conductive substrate or a carbon fiber-containing substrate for metallization, wherein the method of activation is: (a) A step of preparing the substrate processed according to step (II), (b) (i) Dissolved transition metal ions of the first species and additionally their metal particles, (ii) One or more complexing agents, (iii) one or more reducing agents, permanently or temporarily, and (iv) Optionally, one or more second species of dissolved metal ions different from the first species. This is a step to prepare a palladium-free aqueous activated composition containing the following: - At least the first species of the dissolved transition metal ions and the metal particles thereof exist in a reversible equilibrium state, provided that, - The metal particles are formed from the dissolved transition metal ions by continuous or semi-continuous reduction with one or more reducing agents. - The dissolved transition metal ions are formed from the metal particles by continuous or semi-continuous oxidation of the particles, and - The dissolved transition metal ions and the metal particles thereof repeatedly participate in the reduction and oxidation processes, respectively, so that aggregates on which the metal particles precipitate do not form. Process, and (c) A step of bringing the substrate into contact with the activating composition so that a transition metal or transition metal alloy is deposited on the surface of the substrate and an activated surface for metallization is obtained. Methods that include...

2. The method according to claim 1, wherein the majority of the metal particles undergo the oxidation during and / or after step (III)(c).

3. The method according to claim 1 or 2, wherein the first species is copper or cobalt, preferably copper.

4. The method according to any one of claims 1 to 3, wherein the metal particles of the first type in the activating composition are colloidal metal particles.

5. The method according to any one of claims 1 to 4, wherein the metal particles of the first species are formed in situ, continuously or semi-continuously, in the activating composition by reduction after and / or during one or more steps (III)(c) are performed.

6. The method according to any one of claims 1 to 5, wherein the one or more reducing agents include a boron-containing reducing agent, preferably a borohydride.

7. The method according to any one of claims 1 to 6, wherein the one or more reducing agents are added to the activating composition, preferably after one or more steps (III)(c) have been performed, such that further metal particles are formed from the first type of dissolved transition metal ions, each in a continuous or semi-continuous manner.

8. The method according to any one of claims 1 to 7, wherein the dissolved transition metal ions are formed from the metal particles by oxidation by ambient air and / or oxygen gas.

9. The method according to any one of claims 1 to 8, wherein the aqueous acidic rinse composition comprises water and sulfuric acid, or consists of water and sulfuric acid.

10. The method according to claim 9, wherein the aqueous acidic rinse composition does not contain other mineral acids or organic acids or salts thereof.

11. The method according to any one of claims 1 to 10, wherein the aqueous acidic rinse composition has a pH of 1 to 6, preferably 2 to 4.

5.

12. The method according to any one of claims 1 to 11, wherein the step (Ia)(c) of bringing the substrate into contact with the aqueous acidic rinsing composition is performed for 0.5 to 2 minutes.

13. A method for metallizing the activated surface of a non-conductive substrate or a carbon fiber-containing substrate, (A) A step of preparing the nonconductive substrate or the carbon fiber-containing substrate having the activated surface for metallization obtained by the method of any one of claims 1 to 12, and (B) A step of metallizing the activated surface by bringing the activated surface into contact with the first metallization solution so that a first metallized layer is deposited on the activated surface. Methods that include...

14. The method according to claim 13, wherein the first metallization solution in step (B) is a self-catalytic metallized copper solution containing copper ions and a reducing agent.

15. The method according to claim 13 or 14, wherein the substrate obtained after step (B) passes a solder impact test with a defect rate of less than 30%.

Citation Information

Patent Citations

  • Nano copper activation solution and preparation method thereof

    CN107460459A

  • Method for activating non-noble metal colloidal dispersion by controlled oxidation for electroless plating

    US4278712A

  • A method for activating a surface of a non-conductive or carbon-fibres containing substrate for metallization

    WO2020201387A1

  • A method for activating a surface of a non-conductive or carbon-fibres containing substrate for metallization

    WO2022043417A1